Methodological comparison of cancellation versus two-way choice spatial attention tests in humans and dogs - Kis, Anna; Radics, Eszter; Bolló, Henrietta; Topál, József (Frontiers in Veterinary Science, 2023)
Behavioural problems in family dogs are among the leading reasons for relinquishment to shelters which adversely affects animal welfare. Recent research suggests that certain problematic behavioural patterns might be analogous to human psychiatric disorders.Veterinary diagnosis of such conditions, however, is scarce, probably due to the lack of appropriate measurement tools. The current study focuses on dog behaviour resembling the human hemispatial neglect condition, which manifests itself as a deficit in attention to and awareness of one side of the space.Healthy human subjects (N=21) and adult family dogs (N=23) were tested with tools aimed to measure spatial attention. Tests administered to humans included validated paper and pencil neuropsychological tools to assess hemispatial neglect (cancellation tasks), as well as the canine version of that task (visuo-spatial search task). Dogs were tested with the same visuo-spatial search task as well as a two-way choice task.Results show that both in case of dogs and humans the visuo-spatial search task detects individual variation in subjects' side preferences. However, subjects' performance in the different tasks were not related.